Michael A Chaney. Reading Lessons in Seeing: Mirrors, Masks, and Mazes in the Autobiographical Graphic Novel. Jackson: UP of Mississippi, 2016. - Jennifer Caroccio (Studies in 20th & 21st Century Literature, 2017)
Review of Michael A. Chaney. Reading Lessons in Seeing: Mirrors, Masks, and Mazes in the Autobiographical Graphic Novel. Jackson: UP of Mississippi, 2016.
Keywords: Comics; autobiography; memoir; children’s studies; narrative theory